Cytoskeletal stiffening in synthetic hydrogels - Paula de Almeida (Nature Portfolio, 2019)
Although common in biology, controlled stiffening of hydrogels in vitro is difficult to achieve. Here the authors show how a biomimetic hybrid hydrogel can be stiffened instantaneously and reversibly up to 50 times.